Covert Attack Detection and Resilient Control of Quadcopter - Wang, Junhong; Zhou, Sicheng; Xu, Lidan; Zhao, Dong; Guo, Kexin; Yu, Xiang; Guo, Lei (IEEE transactions on industrial informatics, 2025)
This article addresses issues of covert attacks detection and resilient control of quadcopters. In the presence of generalized covert attacks characterized by strong stealth, passive detection techniques prove to be insufficient. Active detection methods are common solutions to this problem, but the balance between the detection capability and the stability of quadcopters still remains as a challenge. Different from the existing active attack detection methods, a coding and channel switching approach and its matched resilient controller for quadcopters are proposed. First, the design and detectability analysis of the coding-based attack detection method are given. Once covert attacks revealed, a secure channel is activated to replace the attacked channel. Second, to enhance quadcopter resilience against covert attacks, a resilient control framework is proposed. It incorporates attack effect estimation and compensation via a fixed-time observer. This framework maintains the stability of the quadcopter's control system under covert attacks. Finally, the numerical simulation and real-world experiments are conducted to evaluate the effectiveness and feasibility of the proposed scheme.